THE EXPERIMENTAL RESEARCH OF INITIAL AND TRANSITIONAL PARTS OF THREEDIMENSIONAL JETS - Isatayev, S.; Tarasov, S.; Toleuov, G.; Isatayev, M.; Asembayeva, M. (Recent Contributions to Physics, 2009)
The work represents the results of experimental research of aerodynamics of three-dimensional turbulent jets flowing from nozzles with rectangle outflow face. The results of measurements of middle and pulse flow characteristics of three-dimensional jets are given. The data on axis speed and turbulence intensity are given and an attempt to uncover their interrelation is made. The results of experimental data comparison on axis speed attenuation of three-dimensional jets with data for axis symmetric stream are presented.